Women in India a search for identity - Rath, Sharada (Ed.); Rath, Navaneeta (Ed.) (New Delhi Anmol, 1999)
This book deals with the problems confronting women from a global perspectives as well as from the Indian angle of vision. The main discussed here are problems facing rural and urban women. The role played by the women in freedom as well as socio cultural
Keywords: Women-India; Women-Sociological aspects; Women in development; Women in politics; Women in mass media